Developing safety and efficiency of work with machinery - Suutarinen, Juha (fi, 1997)
The objective of this pilot study was to find out the possibilities to improve the safety of machinery-related work by improving selecting and use of machinery and developing planning of operations. The reasons for and preventing of accidents, near accidents and interruptions in machinery-related work in plant production were identified. The follow-up data showed that in eight out of fifteen cases technical reasons contributed to worse level of safety. When assessing the accident rate, it was discovered that the accident rate in work with machinery is more than threefold compared to that of all agricultural work. Furthermore, the accident rate of preparing for machinery work is almost quadruple compared to the accident rate of machinery-related work in general.
Keywords: Ra; tapaturmataajuus; työtapaturmat; työturvallisuus; maatalous; maatalouskoneet; agriculture; safety at work; machines; industrial accidents; accident rate